Upaya meningkatkan hasil belajar Pendidikan Kewarganegaraan melalui model pembelajaran talking stick - Boinah, Boinah (Universitas Negeri Yogyakarta, 2017)
This research was conducted to improve students' achievement on Citizenship Education through Talking Stick Instructional Model in Class VII B Muhammadiyah Junior High School Seyegan academic year of 2015/216. It was Classroom Action Research . Based on result of the study it can be concluded that the implementation of Talking Stick Instructional Model improved students' achievement on Citizenship Education. It was based upon the results that (1) the procentage of passer grade was increased through entire cycles. The average of the score was 60.64 with 16.12 % of students succed the defined treshold during pre Cycle, was increased to 79.68 with 65.62 % of students during cycle I and the average of the score was increased to 96.54 consists of 93.54%. (2) The students' learning activities were also increased, cycle I was 46.87% and cycle II became 81.25%. Accordingly, it was recomended that Talking Stick Instructional Model can be used to improve students' achievement on Citizenship Education.